Chains of Gold Portuguese Migration to Argentina in Transatlantic Perspective - Borges, Marcelo J. (Studies in Global Social History, 2009)
Using a systems approach, this book examines how transatlantic labor migrations were linked to European circuits of geographic mobility, and explores the development of social networks that were crucial in Portuguese migrants' socioeconomic adaptation in the Argentine pampas and Patagonia.; Readership: Readers interested in social history and historical sociology; labor history; world and transnational history; migration, ethnic and diaspora studies; history of Latin America, southern Europe, and the Atlantic World.